Design optimization of a pre-combustion CO2 capture plant embedding experimental knowledge. (1st October 2015) - Trapp, Carsten; Thomaser, Timon; van Dijk, H.A.J.; Colonna, Piero
Highlights: A design optimization method for a large-scale pre-combustion CO2 capture plant is demonstrated. Process models are validated against experimental data of a CO2 capture pilot plant. Two-step optimization-based design approach with global and local optimization is adopted. Optimization is performed for various capture rates and different limits of steam/CO ratio. Reduction of specific energy consumption of the capture system by 10% is possible. Abstract: This work is focused on the design optimization of a pre-combustion CO2 capture plant comprising a sweet high-temperature water–gas shift process and an integrated H2 S and CO2 removal process using a mixture of dimethylethers of polyethylene glycol as physical solvent. The steady-state model of the commercial-scale plant has been derived from pilot plant models, which have been extensively validated against experimental data obtained from the pre-combustion CO2 capture facility realized at the Buggenum IGCC power station in the Netherlands. A two-phase optimization-based design approach suited to the use of process simulator environments has been adopted. In the first phase, global design decisions at plant level are evaluated, targeting the minimization of the energy consumption due to CO2 capture. These are the extent of CO conversion in the water–gas shift unit and the percentage of CO2 capture in the removal unit. An optimization of both global design variables is presented considering (i) a wide range of carbon capture targets, (ii) deactivation of catalyst activity throughout the catalyst life and (iii) different operational limits of the steam/CO ratio in the water–gas shift unit. Experimental data from the pilot plant has been used to determine the rate of catalyst deactivation and the operational limits of steam/CO ratio. The second phase of the design procedure targets the local decision variables at unit level. Two studies are presented focusing on: (1) the design of the solvent regeneration and CO2 compression section, and (2) the impact of the solvent temperature on the energy consumption and equipment cost of the removal unit. The design optimization revealed that the specific energy consumption of the pre-combustion capture unit can be reduced by 10% when operating at a minimum molar steam/CO ratio of 1.5 in comparison to the current vendor suggestion of 2.65. These energy savings come at the cost of a lower optimal carbon capture rate, namely 78% instead of 87.5% as reported in the preliminary design.